Discordance in patient and physician global assessment in relapsing polychondritis. (24th September 2021) - Rose, Emily; Ferrada, Marcela A; Quinn, Kaitlin A; Arnaud, Laurent; Goodspeed, Wendy; Kim, Jeff; Allen, Clint; Sirajuddin, Arlene; Chen, Marcus; Grayson, Peter C
Abstract: Objectives: Relapsing polychondritis (RP) is a rare, heterogeneous, systemic inflammatory disease that targets cartilage. Patient-reported outcome measures may differ from physician assessment. This study compared patient global assessment (PtGA) and physician global assessment (PhGA) scores in a prospective cohort of patients with RP. Methods: Adult patients with RP underwent a standardized comprehensive evaluation at ∼6 month intervals. At each visit, three physicians scored PhGA by consensus. The patient independently completed four patient-reported outcomes: PtGA, 36-item Short Form Health Survey (SF-36), Brief Illness Perception Questionnaire (BIPQ) and Multidimensional Fatigue Inventory (MFI). Patient–physician discordance was defined as a difference between PtGA and PhGA of ≥3 on a 0–10 scale. Results: A total of 76 patients were evaluated over 154 visits. The median PhGA was 3 [interquartile range (IQR) 2–3] and the median PtGA was 5 (IQR 4–7). PtGA and PhGA were concordant in 66 visits (42.9%) and patients scored disease severity ≥3 points higher than physicians scored disease activity (positive discordance) in 84 visits (54.5%). Compared with visits with concordance, visits with positive discordance were associated with significantly worse scores on the MFI, BIPQ, SF-36 physical component score and SF-36 mental component score. Conclusion: Patients with RP typically self-report high PtGA that does not align with PhGA. Discordance is likely driven by the high physical and psychological burden of illness experienced by patients. Multifaceted treatment approaches that address the burden of disease in RP from the patient perspective are needed.